Hubungan Kualitas Tidur Dengan Motivasi Belajar Mahasiswa Keperawatan Universitas ‘Aisyiyah Yogyakarta - Tanti Sugiarti; Suryani Suryani; Tiwi Sudyasih (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Sleep quality is a person's satisfaction related to sleep activity that does not show feelings of tiredness, restlessness, lethargy and frequent yawning. Sleep quality in adulthood is different from other ages because it is influenced by activities such as work or college. Learning motivation is the tendency of students to learn in order to achieve optimal results. One of the factors that influences learning motivation is sleep quality. This study aims to determine the correlation between sleep quality and learning motivation of Nursing students at Universitas 'Aisyiyah Yogyakarta. The study was conducted on February 2-5, 2025 with 88 respondents from 711 populations using proportional random sampling techniques. Data were collected through the Pittsburgh Sleep Quality Index (PSQI) questionnaire for sleep patterns and the Motivated Strategies for Learning Questionnaire (MSLQ) for learning motivation. The Kendall Tau test showed a correlation coefficient value (r = 0.308) and a P-value of 0.004 (sig <0.05), which means that there is a significant correlation between sleep quality and learning motivation. The results of this study indicate that the better the sleep quality, the higher the student's learning motivation. Researchers recommend further researches into developing technology-based solutions, such as sleep and study schedule reminder apps, to help students improve their sleep patterns and study motivation.